Sensitive Detection of Thiourea Hazardous Toxin with Sandwich-Type Nafion/CuO/ZnO Nanospikes/Glassy Carbon Composite Electrodes - Mohammed M. Rahman (MDPI AG, 2021)
In this research study, we developed a voltammetric electrochemical sensor probe with a copolymer Nafion (Sulfonated Tetrafluoroethylene-based Fluoro-polymer) decorated with hydrothermally prepared sandwich-type CuO/ZnO nanospikes (NSs) onto a glassy carbon electrode (GCE) for reliable thiourea (TU) detection. The detailed characterizations in terms of structural morphology, binding energy, elemental compositions, grain size and crystallinity for synthesized NSs were performed by field emission scanning electron microscopy (FESEM), X-ray photoelectron spectroscopy (XPS), energy-dispersive X-ray spectroscopy (EDS) and X-ray diffraction (XRD) analysis, respectively. The differential pulse voltammetric (DPV) analysis for TU showed good linearity at current-versus-TU concentration on the calibration plot in the 0.15~1.20 mM range, which is defined as a dynamic detection range (LDR) of TU in a phosphate buffer solution. Considering the slope of LDR over the GCE-coated NSs surface area (0.0316 cm2), the TU sensor sensitivity (0.4122 µA µM−1 cm−2) was obtained. Besides this, the low limit (LOD) for TU detection was calculated and found to be 23.03 ± 1.15 µM. The fabricated Nafion/CuO/ZnO NSs/GCE sensor probe was created as a reliable sensor based on reproducibility, interference effect, stability and response time. Real bio-samples were investigated and the results confirm the anticipated reliability of the TU sensor probe. Thus, this is a noble way to develop enzyme-free electrochemical sensors that could be an alternative approach for the detection of chemicals in the field of enzyme-free biosensor development technology.